Dietary macro and micronutrients associated with MASLD: Analysis of a national US cohort database - Mary Nemer; Fauzia Osman; Adnan Said (Annals of Hepatology, 2024)
Introduction and Objectives: Our objective was to measure and compare the intake of macro and micronutrients in a cohort of individuals with Metabolic Syndrome Associated Steatotic Liver Disease (MASLD) compared with matched controls to identify areas of further research in this area; we identified nutrition-associated associations with MASLD in the United States general population. Materials and Methods: We used the 2017 – 2018 NHANES dataset. Elastography Controlled Attenuation Parameter (CAP score>280) in the absence of other liver disease was defined as MASLD in adults (>18). Advanced fibrosis was defined by transient elastography >10 kPa. Controls were adults without liver disease. Results: 1648 MASLD cases (11.4 % advanced fibrosis) and 2527 controls were identified. MASLD cases were older (P<0.001), more likely males (P = 0.01), less likely to have a college education (P = 0.04) and more likely married (P = 0.002). MASLD cases were more likely to be of Mexican American or Hispanic ethnicity (P = 0.002), have higher BMI, and have higher prevalence of diabetes, hyperlipidemia and hypertension (P<0.001 for all). MASLD cases had higher hs-CRP (P = 0.02) and ferritin (P = 0.02). MASLD cases had lower total (P = 0.004) and added vitamin E in their diet (P = 0.002), lower vitamin K intake (P = 0.005), and higher selenium intake (P = 0.03). Caloric intake (P = 0.04), carbohydrate intake (P = 0.02), cholesterol intake (P = 0.03) and saturated fatty acid intake (P = 0.05) were higher in MASLD. Individuals with MASLD were more likely to be on a diet (P<0.001), sedentary (P = 0.008) and less likely to participate in moderate or vigorous recreational activities (P<0.001). Conclusions: The deficiencies of micronutrients and excess of macronutrients point to oxidative stress, pro-inflammatory state, and lipotoxicity as pathways linking the US diet to MASLD. MASLD patients are more often on special diets, which may reflect prior provider counseling on diet changes to improve health.